2010
DOI: 10.1073/pnas.1001845107
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of an intersubunit electrostatic bond is a critical step in glycine receptor activation

Abstract: Proper regulation of neurotransmission requires that ligandactivated ion channels remain closed until agonist binds. How channels then open remains poorly understood. Glycine receptor (GlyR) gating is initiated by agonist binding at interfaces between adjacent subunits in the extracellular domain. Aspartate-97, located at the α1 GlyR interface, is a conserved residue in the cys-loop receptor superfamily. The mutation of D97 to arginine (D97R) causes spontaneous channel opening, with open and closed dwell times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
(30 reference statements)
1
14
0
Order By: Relevance
“…In the absence of ligand and contaminating Zn 2+ , the D97R receptor displayed spontaneous channel openings grouped into clusters of activity separated by sojourns into what are likely desensitized states. These clusters had a P open of 0.949 ± 0.004 and exhibited the same behavior as first described by Todorovic et al (2010). When saturating concentrations of taurine or glycine were applied, the P open of the clusters increased slightly to 0.990 ± 0.002 and 0.990 ± 0.001, respectively (Figs.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…In the absence of ligand and contaminating Zn 2+ , the D97R receptor displayed spontaneous channel openings grouped into clusters of activity separated by sojourns into what are likely desensitized states. These clusters had a P open of 0.949 ± 0.004 and exhibited the same behavior as first described by Todorovic et al (2010). When saturating concentrations of taurine or glycine were applied, the P open of the clusters increased slightly to 0.990 ± 0.002 and 0.990 ± 0.001, respectively (Figs.…”
Section: Resultssupporting
confidence: 76%
“…This amino acid is conserved across the entire cys-loop subunit superfamily, residing at a subunit interface near residues previously implicated in ligand binding (Brejc, 2001). Our previous work strongly suggested that D97 forms an intersubunit electrostatic bond with R119 (Todorovic et al, 2010), a residue earlier shown to play a role in determining glycine affinity (Grudzinska et al, 2005). In our previous study we engineered cysteine mutations at the D97 and R119 positions, and used those to show that receptor function could be markedly affected by addition of oxidizing, cross-linking or reducing agents (Todorovic et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is therefore not surprising that destabilizing the interface by mutation can lead to spontaneous channel activation (Miller et al 2008;Todorovic et al 2010).…”
Section: The Role Of Loop Cmentioning
confidence: 99%
“…Laha and Wagner at ASPET Journals on May 12, 2018 molpharm.aspetjournals.org dependent intersubunit electrostatic interaction (Todorovic et al, 2010). This interaction is proposed to exist when the glycine receptor is in the unbound state and is broken upon the binding of agonist.…”
mentioning
confidence: 99%